Dinamika Relasi Agama Dan Gerakan Sosial Dalam Konteks Masyarakat Multikultural - Khaerul Anam; Asep Muhamad Iqbal; Dadang Kuswana (Yayasan Cendekia Gagayunan Indonesia, 2024)
This research aims to analyze the interaction between religion and social movements in culturally diverse societies. In a multicultural context, religion often serves as a driver or inhibitor for social movements. This research will use a qualitative approach with a literature study method using existing related literature and documents, in the form of books, scientific journals, articles, previous research reports, and other relevant sources. Primary and secondary data sources are obtained from books and scientific journals related to the sociology of religion, social anthropology, and multiculturalism studies. The data analysis technique uses content analysis to identify and analyze the main patterns, themes, or categories of the text or literature studied. The results showed that religion can strengthen group identity and social mobilization, but it can also lead to intergroup conflict. Social movements, both reformist and conservative, often draw inspiration from religious values. In some cases, social movements have been able to create spaces for constructive interfaith dialogue, promoting understanding and tolerance between different groups. Conversely, tensions that arise between religious practices and social values can lead to polarization within society. Therefore, it is important to understand these dynamics in order to create a harmonious and inclusive society. This research contributes to the development of theories of religion and social movement relations, as well as offering practical insights for stakeholders in dealing with multicultural challenges.